Recycling of pultrusion production waste into innovative concrete-polymer composite solutions - Ribeiro, Maria Cristina Santos (2014)
In this study, the added value resultant from the incorporation of pultrusion production waste into polymer based concretes was assessed. For this purpose, different types of thermoset composite scrap material, proceeding from GFRP pultrusion manufacturing process, were mechanical shredded and milled into a fibrous-powdered material. Resultant GFRP recyclates, with two different size gradings, were added to polyester based mortars as fine aggregate and filler replacements, at various load contents between 4% up to 12% in weight of total mass. Flexural and compressive loading capacities were evaluated and found better than those of unmodified polymer mortars. Obtained results highlight the high potential of recycled GFRP pultrusion waste materials as efficient and sustainable admixtures for concrete and mortar-polymer composites, constituting an emergent waste management solution.